Research on the Prediction of Health Status of the Container Gantry Crane Energy Systems - Jia, Hongxia; Liu, Haiwei; Yang, Yang (Journal of coastal research, 2015)
Jia, H.; Liu, H., and Yang, Y., 2015. The research on the prediction of health status of the container gantry crane energy systems. In this paper, the remaining capacity of lead-acid batteries is used to evaluate the health status of RTG energy systems. A LS-SVM model was established for predicting the remaining capacity of batteries, with the PSO-BP algorithm optimizing the parameters in the LS-SVM model. Using the trained LS-SVM model, the remaining capacity of batteries and the degradation trend of battery capacity with time are predicted. Compared with measured results, the predicted results show that the LS-SVM model can accurately predict the remaining capacity of lead-acid batteries.